PENGARUH KEBIJAKAN DIVIDEN, STRUKTUR KEPEMILIKAN, DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN DALAM PERSPEKTIF TEORI AGENSI DAN TEORI SIGNALING - WONGSO, AMANDA (Universitas Katolik Widya Mandala Surabaya, 2012)
This study aims to see the effect of dividend policy; ownership structures includes managerial and institutional ownership, and debt policy towards value of the firm. This study uses secondary data of 33 indexes LQ 45 companies listed on the Indonesia Stock Exchange during the three-year period 2009-2011 as samples and have met certain criteria. The results shows that the ownership structures both managerial and institutional ownership, and debt policy do not affect the value of the firm. Only dividend policy that positive significantly affects to the value of the firm.